Standardization of A Sample-Processing Methodology for Stable Isotope Studies in Poultry - Denadai,JC (2019)
ABSTRACT The objective of this study was to determine if lipid extraction processes alter the isotopic value of δ13C and δ15N of tissues (pectoral muscle, thigh and liver) and eggs and if the use of anticoagulants interferes with blood and plasma δ13C and δ15N isotopic values. Samples were acquired from the same flock of birds. The 32 egg samples were randomly divided into four treatments (liquid, dehydrated, and fat-extracted with ether or chloroform + methanol) with eight replicates each. The 24 samples of pectoral muscle, thigh muscle and liver of broilers were randomly divided into three treatments (dehydrated, fat-extracted with ether and chloroform + methanol) with eight replicates each. Blood samples were divided into a 3x3 factorial arrangement with three physical forms (liquid, oven-dried or freeze-dried) and three collection methods (with no anticoagulant, with EDTA or heparin). Plasma samples were distributed in a 3x2 factorial arrangement, with three physical forms (liquid, oven-dried, or freeze-dried) and two anticoagulants (EDTA or heparin). The obtained isotopic results were submitted to the multivariate analysis of variance (MANOVA) and univariate (ANOVA, complemented by Tukey’ test), using the GLM procedure of the statistical program SAS (1996) or Minitab 16. The results show that it is possible to use the evaluated methods of fat extraction, drying and anticoagulants in the isotopic analyses of carbon-13 and nitrogen-15 in chicken tissues.